Menthol Cigarette Smoke Induces More Severe Lung Inflammation Than Non-menthol Cigarette Smoke Does in Mice With Subchronic Exposure – Role of TRPM8 - Lin, An-Hsuan; Liu, Meng-Han; Ko, Hsin-Kuo; Perng, Diahn-Warng; Lee, Tzong-Shyuan; Kou, Yu Ru (Frontiers in Physiology, 2018)
Menthol cigarette smoking is associated with more severe lung inflammation than non-menthol cigarette smoking is in smokers with chronic obstructive pulmonary disease. However, the mechanisms remain unclear. Menthol is a ligand of transient receptor potential melastatin-8 (TRPM8), which is also sensitive to reactive oxygen species (ROS). Our recent in vitro study demonstrated that the extracts of menthol cigarette smoke (M-CS) can induce greater ROS-sensitive, TRPM8-mediated, mitogen-activated protein kinase (MAPK)-dependent inflammatory responses in lung epithelial cells than the extracts of non-menthol cigarette smoke (Non-M-CS) can. In this study, we tested the hypothesis that M-CS can induce more severe lung inflammation than Non-M-CS can via the additional action of menthol in M-CS on epithelial and lung TRPM8 in mice. Compared with Non-M-CS exposure, subchronic M-CS exposure for seven days up-regulated the epithelial and lung expression of TRPM8, induced more vigorous activation of epithelial and lung MAPKs, and caused more severe lung inflammation. The MAPK activation was evidenced by the increased expression of phosphor-extracellular signal-regulated and phosphor-c-Jun N-terminal kinases. The lung inflammation was evidenced by pathohistological findings and increases in several inflammatory indices. Moreover, treatment with a TRPM8 antagonist (N-(3-aminopropyl)-2-[(3-methylphenyl)methyl]oxy-N-(2-thienylmethyl)benzamide; AMTB) greatly suppressed the MAPK activation and lung inflammation induced by Non-M-CS and M-CS, and no differences were noted in the residual responses to these two types of CS. Conversely, the levels of biomarkers of acute CS exposure (20 min), including carboxyhemoglobin and cotinine (a nicotine metabolite) in blood plasma, and superoxide and hydrogen peroxide (two major types of ROS) in bronchoalveolar lavage fluid, did not show significant differences in the mice with Non-M-CS and M-CS exposure. We concluded that M-CS could induce greater TRPM8-mediated activation of MAPKs and lung inflammation than Non-M-CS could in mice with subchronic exposure. The augmented inflammatory effects of M-CS are unlikely due to a larger total amount of CS inhaled, but may be caused by an additional stimulation of epithelial and lung TRPM8 by menthol in M-CS. A common stimulant (presumably ROS) generated by both CS types may also stimulate TRPM8, activate MAPKs, and induce lung inflammation because treatment with AMTB could reduce these responses to Non-M-CS.